1996
DOI: 10.1055/s-2007-979872
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Tissue Localization, Distribution and Turnover to Feeding After Intraperitoneal125I-Leptin Administration toob/obanddb/dbMice

Abstract: Brain and whole body localization and distribution of 125I-leptin was determined after intraperitoneal administration to ob/ob and db/db mice, and was compared to inhibition of food intake. Food intake was not significantly inhibited at3 hours post-injection, but was decreased significantly at 6 h (p < 0.0007) and 24 h (p < 0.02) in ob/ob mice, times at which > 97 % of the radioactive dose was found in the urine. The highest concentrations of 125I-leptin at all time-points were found in the serum, liver and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 5 publications
(9 reference statements)
1
16
0
Order By: Relevance
“…Areas under the bi-exponential equation curve provide values consistent with Other reports of leptin pharmacokinetics and tissue distribution in rodents have used very high doses of recombinant leptin administered with the tracer. 8, 15 Cumin et al 8 used recombinant leptin at three supraphysiological doses (0,25, 0.5 and 1.0 mgakg), with the lowest of these, corresponding to approximately 1000 times the level of endogenous leptin. The primary aim of their study was to determine whether the major clearance process of leptin was via the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Areas under the bi-exponential equation curve provide values consistent with Other reports of leptin pharmacokinetics and tissue distribution in rodents have used very high doses of recombinant leptin administered with the tracer. 8, 15 Cumin et al 8 used recombinant leptin at three supraphysiological doses (0,25, 0.5 and 1.0 mgakg), with the lowest of these, corresponding to approximately 1000 times the level of endogenous leptin. The primary aim of their study was to determine whether the major clearance process of leptin was via the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…A study in humans reported a half-life of circulating leptin of 25 min. 18 Two studies in mice suggested the considerably longer half-lives of 1.5 and 3 h, 19,20 whereas a recently published study in Zucker rats reported a much shorter half-life of circulating leptin ( $ 6 min) with no difference between lean and obese animals. 21 Much of the disparity in the literature is attributable to a wide range of methodologies and study objectives, with half-life being determined secondarily, often based on a minimal number of time points.…”
Section: Introductionmentioning
confidence: 99%
“…In diet induced obese mice, the circulating leptin was significantly elevated with the increase of body weight. Studies also showed these mice are resistant to peripherally administrated leptin (Van Heek et al, 1996). Compared to normal weight people, obese people usually developed hyperleptinemia and leptin resistant, which might due to a defect in transporting of leptin through the blood barrier (Banks et al, 1996;Caro et al, 1996).…”
Section: Leptinmentioning
confidence: 99%